Pemahaman konsep siswa SMP dalam menyelesaikan masalah matematika berdasarkan kemampuan matematika - Jagom, Yohanes Ovaritus; Lakapu, Meryani; Djong, Kristoforus D; Uskono, Irmina V; Dosinaneng, Wilfridus B N (Prosiding Seminar Nasional Matematika dan Pendidikan Matematika, 2021)
This research is a qualitative research that aims to analyze the understanding of mathematical concepts of junior high school students in solving math problems. The subjects in this study consisted of three students with high, medium, and low mathematical abilities. Research subjects were also selected according to the results of discussions between mathematics teachers and researchers. Data collection is in the form of concept understanding test results and interview results based on indicators of understanding mathematical concepts. Data analysis includes data reduction, data presentation, and drawing conclusions. Checking the validity of the data using time triangulation. The results of data exposure and analysis concluded that (1) students with high mathematical abilities were able to complete the concept understanding test and meet the three indicators of concept understanding, namely indicators of translation (translation), interpretation (interpretation), extrapolation (extrapolation). (2) students with moderate mathematical ability students with high mathematical abilities were able to complete the concept understanding test and meet the three indicators of concept understanding, namely indicators of translation (translation), interpretation (interpretation), extrapolation (extrapolation). (3) students with low ability only meet one indicator, namely translation. Therefore, the researcher suggests that students should always practice solving problems according to the steps or concepts in learning mathematics in order to improve their mathematical abilities.